2021
DOI: 10.1007/s11356-021-17033-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polypropylene, polyvinyl chloride, polyethylene terephthalate, polyurethane, high-density polyethylene, and polystyrene microplastic on Nelumbo nucifera (Lotus) in water and sediment

Abstract: Plastic waste is recognised as hazardous, with the risk increasing as the polymers break down in nature to secondary microplastics or even nanoplastics. The number of studies reporting on the prevalence of microplastic in every perceivable niche and bioavailable to biota is dramatically increasing. Knowledge of the ecotoxicology of microplastic is advancing as well; however, information regarding plants, specifically aquatic macrophytes, is still lacking. The present study aimed to gain more information on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Most current reports on the toxicity of MPs focus on PS, while the biological safety assessment of PP is mainly concentrated on aquatic organisms [ 33 , 34 , 35 ] and plants [ 36 , 37 ]. Previous studies have reported that PP-MPs can reduce the thickness of the intestinal mucosa and intestinal muscle layer, cause oxidative stress and inflammation in intestinal tissue, and seriously interfere with lipid metabolism in zebrafish [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most current reports on the toxicity of MPs focus on PS, while the biological safety assessment of PP is mainly concentrated on aquatic organisms [ 33 , 34 , 35 ] and plants [ 36 , 37 ]. Previous studies have reported that PP-MPs can reduce the thickness of the intestinal mucosa and intestinal muscle layer, cause oxidative stress and inflammation in intestinal tissue, and seriously interfere with lipid metabolism in zebrafish [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of MPs on the environment and ecosystem depend on the types of polymers involved because they have varied toxicity levels (Montoto-Martínez et al 2020 ). According to Zimmermann et al ( 2019 ), extracts obtained from PVC and PUR were with highest toxicity, while PET and HDPE were either non- or slightly toxic (Esterhuizen and Kim 2022 ). In agreement with this assertion, Yuan et al ( 2022 ), as well as the Interreg Central Baltic (in association with the European Union) in ( 2018 ) listed PUR, PAN, and PVC among the top-ranking hazardous polymers used for plastic production, while others such as PP, PE, PEVA (ethylene–vinyl acetate), and polyvinyl acetate were regarded as the least toxic.…”
Section: Resultsmentioning
confidence: 99%
“…Given the limited data on the impacts of microplastics on soil invertebrates, systematic investigations of the influence of particle properties on the ecotoxicological behavior of microplastic in soil are rare and the determination of toxicity mechanisms related to microplastic properties accordingly difficult. Studies using bacteria (Aliivibrio fischeri), plants (Nelumbo nucifera) or fish (Danio rerio) suggest that PVC is more toxic than PS (Lei et al, 2018;Zimmermann et al, 2019;Esterhuizen and Kim, 2022), but this could not be shown for soil invertebrates. Several studies demonstrated that PS affects the cellular responses of soil organisms (Sobhani et al, 2021b;Jiang et al, 2020;Wang et al, 2019;Xu et al, 2021a; Table 4), but a direct comparison of the effects of PS vs those of other polymers is difficult, as in the respective studies the PS particles were smaller (<250 µm) than particles of other microplastic types (e.g.…”
Section: Role Of the Properties Of Microplastics (Polymer/shape/size)mentioning
confidence: 98%